UPAYA KERJASAMA INDONESIA – FILIPINA DALAM MENGATASI PRAKTEK ILLEGAL FISHING DI PERAIRAN INDONESIA PERIODE 2007-2011 - Putri, Leonita Ersanti; Windiani, Reni; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Illegal fishing by foreign ships in Indonesia is often committed by neighbor countries,such as Philippines. Illegal fishing issue in Indonesia is an important transnationalcrime because it can threaten the ecosystem and the economy. IndonesianGovernment has made many efforts to stop illegal fishing, including by cooperatingwith Philippines in marine and fisheries. Solving Illegal, Unreported, UnregulatedFishing (IUUF) practice is one of the research issues from the implementation ofIndonesia-Philippines cooperation. This undergraduate thesis used qualitativeresearch method with descriptive qualitative data analysis. The data collectiontechniques are interview with related parties and processing various data, as well asliterature study, which is accumulating data from various literatures, such as books,journals, scientific articles, agreements, scientific papers, websites related to theissue. The result of this research is based on on international cooperation theory byparadigm liberalism and shows that due to increased illegal fishing in Indonesia in2007-2011, particularly by Philippines fishers, the governments of the Republic ofIndonesia-the Republic of Phillipines established a cooperation which is outlined inan MoU to solve illegal fishing. Despite the cooperation, the implementation wasn’teffective due to internal and external factors from both countries.